Batman. Vol. 4, The cowardly lot - Tynion, James, IV (DC Comics, 2023)
"Is the new gang in Gotham connected to the resurgence of the Scarecrow? Meanwhile, Mayor Nakano has a meeting with shadowy billionaire Simon Saint, who has come to Gotham to pitch the concept of an advanced law enforcement project know as...the Magistrate!"--